Pierre Gwa - Mpyemõ Guitarist: His Songs and Their Sources Central African Republic, 1966 - Kubik, Gerhard (International Library of African Music, 2007)
Early acoustic guitar styles in central Africa. As far as we can reconstruct, the acoustic guitar styles of central Africa sprang up and gained momentum shortly after World War II, first only in a few areas that can be pinpointed on a map (Kubik 1965). These were places of colonial economic activity; mining centres, urban areas, trading posts and so on. people from various parts of the region were attracted to these centres in search of work. The multi-ethnic background of such urban and semi-urban melting pots promoted the use of vehicular, or trade, languages. It was in such places that, besides other commodities, guitars became available in shops, and it was here that the need arose for entertainment in the workers' milieu using a lingua franca such as Lingala (in western parts of the present Democratic Republic of the Congo, and across the river at Brazzaville) or Swahili in its Kingwana version (in Katanga), or Icibemba (on the Zambian side of the Copperbelt).
Keywords: Central Africa; African Music; Zambia; Democratic Republic of the Congo